Farro in Italy: A desk-study - Buerli, M. (2007)
Farro, also known as 'hulled wheats' (einkorn, emmer and spelt) are among the most ancient cereal crops of the Mediterranean region (Perrino et al. 1996). These cereals were popular within the region for hundreds of years and remained a staple food for a long time until they eventually fell into disuse. However, farro is now becoming popular again. In Italy, farro is attracting farmers' interest due to its high commercial potential. The industrial sector is also looking to farro because of its potential in the production of pasta, biscuits and other items.